2023
DOI: 10.1371/journal.pone.0283861
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and impact of physical activity interventions during substance use disorder treatment excluding tobacco: A systematic review

Abstract: Substance use disorder is a worldwide issue that entails negative health and physical activity is a promising complementary therapy for alleviating the consequences. The objective of this reviews is to characterize physical activity interventions offered in the literature and explore their effects during treatment for people with substance use disorders with excluding studies focusing only on tobacco use. A systematic search of seven databases on articles including a physical activity intervention during a tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 74 publications
2
8
0
Order By: Relevance
“…Our findings on the inverse relationship between physical activity and substance co-use among adolescents align with global studies that suggest active participation in physical activities serves as a protective factor against substance use [ 29 , 30 ]. This relationship highlights the extensive benefits of physical activity, which go beyond physical health to encompass mental health and social well-being [ 31 ].…”
Section: Discussionsupporting
confidence: 88%
“…Our findings on the inverse relationship between physical activity and substance co-use among adolescents align with global studies that suggest active participation in physical activities serves as a protective factor against substance use [ 29 , 30 ]. This relationship highlights the extensive benefits of physical activity, which go beyond physical health to encompass mental health and social well-being [ 31 ].…”
Section: Discussionsupporting
confidence: 88%
“…Physical exercise, emerging as a novel intervention for patients with SUD, has proven effective (Dowla et al, 2022). A previous systematic review from Piché et al (2023) has suggested that most common physical activity intervention during SUD treatment identified was of moderate intensity, 3 times per week (≈ 1 h) for 13 weeks, leads to a similar conclusion of the present study. Another meta-analysis on the effects of exercise of different intensities on withdrawal symptoms among people with SUD indicated that different intensity exercise reduced depression after the intervention with moderate-intensity exercise producing the best effect, while only light-and moderate-intensity exercise relieved anxiety (Li et al, 2023).…”
Section: Discussionsupporting
confidence: 80%
“…Some studies report reductions in craving and substance use (Piché et al, 2023;Rensburg et al, 2009Rensburg et al, , 2013, psychological distress and symptoms of mental ill-health (Paluska & Schwenk, 2000;Saxena et al, 2009), as well as increased quality of life, selfesteem, relapse prevention efficacy, and perceived physical health and psychological wellbeing (Furzer et al, 2021),. However, other studies found no significant changes in anxiety, depression, self-efficacy and substance use behaviour (Colledge et al, 2018;Giménez-Meseguer et al, 2020;Linke & Ussher, 2015;Piché et al, 2023;Thal et al, 2023;Thompson et al, 2020). Overall, studies of PA in SUD treatment are highly heterogenous, demonstrating high risk of bias (Piché et al, 2023;Thal et al, 2023;Thompson et al, 2020).…”
Section: Background and Rationalementioning
confidence: 99%